Voltage Differencing Gain Amplifier-Based Shadow Filter: A Comparison Study - Moonmuang, Pitchayanin; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2020)
This study determines the voltage-mode shadow filter realization based on voltage differencing gain amplifier (VDGA) in comparison with a classical second-order filter. The realized shadow filter uses three VDGAs and only two grounded capacitors, and can simultaneously realize second-order lowpass and bandpass filter responses. The natural angular frequency (ωA) and the quality factor (QA) can be tuned by means of the VDGAs' transconductance gains. The performance comparison between the realized shadow filter and the classical second-order filter is demonstrated through simulation results with 0.25μm CMOS technology.
Keywords: Second-order filter; Shadow filter; Voltage differencing gain amplifier (VDGA); Voltage-mode circuit